ENTREPRENEURSHIP DEVELOPMENT FOR STUDENTS - Hastuti, Indra; Utami, Indah Wahyu; Sopingi, Sopingi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The development of proper entrepreneurship for students in order to produce independent and sustainable entrepreneurs is needed because there are many ideas and creativity of students to open a business, but they stop at the last activity of lectures, namely the entrepreneurship bazaar. Problems with limited manpower, timely service, marketing and place of business make their business unsustainable. The purpose of this activity is to develop entrepreneurial programs run by students who are profitable and can create jobs and assist the government in alleviating unemployment and poverty. The result of this Entrepreneurship Development Program activity is that 20 student tenants have been formed.